The mediator role of customer satisfaction in the effect of gastronomic image on behavioral intention - Gökhan Onat; Ebru Guneren (Tourism & Management Studies)
In recent years, it has become evident that gastronomic tourism plays a crucial role in destination development. The primary objective of this study is to investigate the impact of a destination's gastronomy image on behavioral intentions toward that destination and to explore whether customer satisfaction potentially serves as a mediating factor. Within this context, we examined the effects of various components contributing to a destination's gastronomic image, such as culinary culture, food and beverage businesses, and gastronomy activities, on behavioral intentions. We also explored the mediating role of customer satisfaction using SPSS and AMOS software. The research findings conclusively show that a destination's gastronomy image significantly influences behavioral intentions, with customer satisfaction partially mediating this influence. Based on the study's results and comparative discussions, we offer recommendations to the relevant literature, destination management entities, businesses in the gastronomy sector, and tourism policy makers. It is anticipated that the implementation of these suggestions will enhance the gastronomic image of destinations, increase overall satisfaction levels, and consequently, boost behavioral intentions.